Investigating the Financial Inclusion, Domestic Investment, and Financial Development Nexus in Nigeria - Anthony-Orji, Onyinye; Orji, Anthony; Jude, Ikubor O.; Ogbuabor, Jonathan E. (Unisia, 2023)
Nigeria is a developing nation with a population of over 200 million. Of this aggregate, approximately 106 million are aged 18 years and above. Of this adult population, 70 million live in rural areas, and many do not have adequate access to relevant financial products and services. The proportion of individuals and firms that use or have access to financial services can be referred to as financially inclusive. This study analyzes the impact of financial inclusion and domestic investment on Nigeria’s financial development. Multiple regression analysis was employed in this study which spanned over the period, 1982-2021. The empirical results reveal that financial inclusion and domestic investment have positive impacts on financial development; however, domestic investment has a more significant impact to a larger extent. The study recommended that policies should be directed towards creating a more inclusive financial system to improve the current level of financial inclusion to achieve better financial development in Nigeria. This study concludes that governments should formulate policies that boost financial inclusion and investment to deepen the level of financial development in the economy.